Tcp performance in coded wireless mesh networks with cope implementation: An overview (International Journal of Engineering and Computer Science, 2013)
This paper investigates the benefit of network coding for TCP traffic in a wireless mesh network. COPE, a new architecture for wireless mesh networks is also introduced. Packets are mixed (i.e., coded) by routers from different source nodes to increase the information content during every transmission. Intelligently mixing the packets increase network throughput. The results show that COPE largely increases network throughput. Depending on the traffic pattern, congestion level, and transport protocol used, gains in throughput vary. Network coding not only reduces the number of transmissions by sending multiple packets via a single transmission but also results in a smaller loss probability due to reduced contention on the wireless medium. Coding opportunity can be increased by inducing small delays at intermediate nodes. However, this extra delay at intermediate nodes results in longer round-trip-times that adversely affect TCP throughput.